2020
DOI: 10.1002/anie.202012513
|View full text |Cite
|
Sign up to set email alerts
|

A Gold Nanoparticle Nanonuclease Relying on a Zn(II) Mononuclear Complex

Abstract: Similarly to enzymes,f unctionalized gold nanoparticles efficiently catalyze chemical reactions,hence the term nanozymes.H erein, we present our results showing how surface-passivated gold nanoparticles behave as synthetic nanonucleases,a ble to cleave pBR322 plasmid DNAwith the highest efficiency reported so far for catalysts based on asingle metal ion mechanism. Experimental and computational data indicate that we have been successful in creating acatalytic site precisely mimicking that suggested for natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 69 publications
2
30
0
Order By: Relevance
“…We have observed that this is indeed the case for very challenging substrates such as DNA. [10] Our results show how very subtle changes, in both the catalyst and substrate, may significantly affect the mechanism of metal ion catalyzed cleavage of RNA phosphodiesters.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…We have observed that this is indeed the case for very challenging substrates such as DNA. [10] Our results show how very subtle changes, in both the catalyst and substrate, may significantly affect the mechanism of metal ion catalyzed cleavage of RNA phosphodiesters.…”
Section: Discussionmentioning
confidence: 81%
“…However, the binding of the nucleobase to a nearby Zn(II) complex makes it unavailable for cooperating in the cleavage of the substrate. We have shown that phosphate diesters (but not triesters) [23] cleavage by TACN−Zn(II) complexes requires a dinuclear catalytic site [10,12,18,19] . As the concentration of UPNP increases, dinuclear catalytic sites become less and less available and the catalytic performance of the catalyst decreases (downward curvature of the graph of Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported in the past that gold nanoparticles (AuNPs) functionalized with metal ion complexes are powerful catalysts of the cleavage of phosphate diester including DNA. [9][10][11] We thought they were excellent candidates as catalysts for the cleavage of phosphate triesters and nerve agents, in particular. Typically, catalysts developed for this purpose are not tested with the real nerve agents for their toxicity and simulants, far less toxic, are used.…”
Section: Introductionmentioning
confidence: 99%